A Watermarking Algorithm for Multiple Watermarks Protection Using SVD and Compressive Sensing - Thanki, Rohit; Dwivedi, Vedvyas; Borisagar, Komal; Borra, Surekha (Informatica, 2017)
In this paper, a watermarking algorithm is proposed and analyzed using RDWT-SVD and Compressive Sensing for multiple watermarks protection. In this algorithm, the multiple watermarks are inserted into single host medium. Here three watermarks are converted into its CS measurements using compressive sensing procedure before embedding into host medium. The CS measurements of watermarks are generated using discrete cosine transform (DCT) and normal distribution matrix. The singular value of these CS measurements of multiple watermarks is inserted into the singular value of approximation wavelet coefficients of R channel, G channel and B channel of color host image to get watermarked color image. The experimental results show that this proposed algorithm is equally worked for all types of watermarks. This proposed algorithm also provides robustness against various watermarking attacks and performed better than existed algorithms in the literature.